In a 'Real-World', Clinic-Based Community Setting, Sorafenib Dose of 400 mg/day is as Effective as Standard Dose of 800 mg/day in Patients with Advanced Hepatocellular Carcimona, with Better Tolerance and Similar Survival. (2013) - Shingina, Alexandra; Hashim, Al Moutaz; Haque, Mazhar; Suen, Michael; Yoshida, Eric M; Gill, Sharlene; Donnellan, Fergal; Weiss, Alan A
Abstract : BACKGROUND: Sorafenib, an oral multityrosine kinase inhibitor, has been approved for treatment of unresectable hepatocellular carcinoma (HCC). British Columbia (BC) was the first province in Canada to provide drug coverage for sorafenib. OBJECTIVE: To review the BC experience with sorafenib to assess its effectiveness and tolerance in a 'real-world' clinical setting. METHODS: A retrospective clinic chart review identified 99 patients referred to the BC Cancer Agency from 2008 to 2010 with a diagnosis of HCC who qualified for treatment with sorafenib. RESULTS: Therapy with sorafenib was initiated and continued at a reduced dosage of 400 mg/day in 66 of 99 patients, with 22 patients requiring further dose reduction. Full- and reduced-dose group patients had similar baseline characteristics, except for a higher proportion of female patients (P=0.02) and individuals with alcoholic liver disease (P=0.04) in the full-dose group. The incidence of any grade of adverse effects was higher in the full-dose group (94% versus 77% in the reduced-dose group; P=0.04). Dose reduction rates were significantly higher in the full-dose group, occurring in 66% versus 24% of reduced-dose group patients (P=0.001). The overall survival rates were similar between the two groups: 7.8 months versus 7.1 months in full- versus reduced-dose groups (P=0.14), as were radiological progression rates and alpha-fetoprotein levels. CONCLUSIONS: In a review of 99 patients in a 'real-world' community setting, a sorafenib dose of 400 mg/day was better tolerated and had similar efficacy compared with a sorafenib dose of 800 mg/day with respect to survival and outcomes.